Distinct synaptic and neurochemical changes to the granule cell-CA3 projection in Bassoon mutant mice - Dieni, Sandra; Nestel, Sigrun; Sibbe, Mirjam; Frotscher, Michael; Hellwig, Sabine (Frontiers in Synaptic Neuroscience, 2015)
Proper synaptic function depends on a finely-tuned balance between events such as protein synthesis and structural organization. In particular, the functional loss of just one synaptic-related protein can have a profound impact on overall neuronal network function. To this end, we used a mutant mouse model harboring a mutated form of the presynaptic scaffolding protein Bassoon (Bsn), which is phenotypically characterized by: (i) spontaneous generalized epileptic seizure activity, representing a chronically-imbalanced neuronal network, and (ii) a dramatic increase in hippocampal brain-derived neurotrophic factor (BDNF) protein concentration, a key player in synaptic plasticity. Detailed morphological and neurochemical analyses revealed that the increased BDNF levels are associated with: I. modified neuropeptide distribution, II. perturbed expression of selected markers of synaptic activation or plasticity, III. subtle changes to microglial structure, and IV. morphological alterations to the mossy fiber synapse. These findings emphasize the important contribution of Bassoon protein to normal hippocampal function, and further characterize the Bsn mutant as a useful model for studying the effects of chronic changes to network activity.